Initial electric field changes of lightning flashes in tropical thunderstorms and their relationship to the lightning initiation mechanism - Sabri M.H.M.; Ahmad M.R.; Esa M.R.M.; Periannan D.; Lu G.; Zhang H.; Cooray V.; Williams E.; Aziz M.Z.A.A.; Abdul-Malek Z.; Alkahtani A.A.; Kadir M.Z.A.A.B. (Elsevier Ltd, 2023)
Antennas; Lightning; Thunderstorms; Tropics; Electric field change; Fast positive breakdown; Initial breakdown pulse; Narrow bipolar events; Negative breakdown; Electric fields; amplitude; electric field; lightning; thunderstorm; Florida [United States]; United States